1998
DOI: 10.1128/jb.180.7.1947-1950.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Active-Site Cysteines of the Periplasmic Thioredoxin-Like Protein CcmG of Escherichia coli Are Important but Not Essential for Cytochrome c Maturation In Vivo

Abstract: A new member of the family of periplasmic protein thiol:disulfide oxidoreductases, CcmG (also called DsbE), was characterized with regard to its role in cytochrome c maturation in Escherichia coli. The CcmG protein was shown to be membrane bound, facing the periplasm with its C-terminal, hydrophilic domain. A chromosomal, nonpolar in-frame deletion in ccmG resulted in the complete absence of all c-type cytochromes. Replacement of either one or both of the two cysteine residues of the predicted active site in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…CcmG is a 20-kDa protein with an N-terminal membrane anchor and faces the periplasm with its hydrophilic C-terminal domain containing the active site ( Fig. 2B) [89]. Around the C-X-X-C motif several additional residues are conserved between CcmG and the reductases Trx1 and DsbD, suggesting that CcmG also assumes the thioredoxin fold ( Fig.…”
Section: Ccmg and Ccmh: Specialised Oxidoreductasesmentioning
confidence: 99%
See 4 more Smart Citations
“…CcmG is a 20-kDa protein with an N-terminal membrane anchor and faces the periplasm with its hydrophilic C-terminal domain containing the active site ( Fig. 2B) [89]. Around the C-X-X-C motif several additional residues are conserved between CcmG and the reductases Trx1 and DsbD, suggesting that CcmG also assumes the thioredoxin fold ( Fig.…”
Section: Ccmg and Ccmh: Specialised Oxidoreductasesmentioning
confidence: 99%
“…In E. coli, it has been shown that ccmG mutants having one or both cysteine residues of the active site replaced by serine produce strongly decreased levels of holocytochrome c. Furthermore, cytochrome c maturation could be restored when CcmG active-site mutants were grown in the presence of reducing compounds such as cysteine or 2-mercaptoethanesulfonic acid. Remarkably, a ccmG in-frame deletion mutant was irreversibly defective [89,94,98]. In R. capsulatus, the active-site mutants were tested under conditions of photosynthetic growth, for which c-type cytochromes are absolutely essential, and shown to be lethal under these conditions [92].…”
Section: Ccmg and Ccmh: Specialised Oxidoreductasesmentioning
confidence: 99%
See 3 more Smart Citations